# Theory HOL-Computational_Algebra.Normalized_Fraction

(*  Title:      HOL/Computational_Algebra/Normalized_Fraction.thy
Author:     Manuel Eberl
*)

theory Normalized_Fraction
imports
Main
Euclidean_Algorithm
Fraction_Field
begin

lemma unit_factor_1_imp_normalized: "unit_factor x = 1  normalize x = x"
using unit_factor_mult_normalize [of x] by simp

definition quot_to_fract :: "'a × 'a  'a :: idom fract" where
"quot_to_fract = (λ(a,b). Fraction_Field.Fract a b)"

definition normalize_quot :: "'a :: {ring_gcd,idom_divide,semiring_gcd_mult_normalize} × 'a  'a × 'a" where
"normalize_quot =
(λ(a,b). if b = 0 then (0,1) else let d = gcd a b * unit_factor b in (a div d, b div d))"

lemma normalize_quot_zero [simp]:
"normalize_quot (a, 0) = (0, 1)"

lemma normalize_quot_proj:
"fst (normalize_quot (a, b)) = a div (gcd a b * unit_factor b)"
"snd (normalize_quot (a, b)) = normalize b div gcd a b" if "b  0"
using that by (simp_all add: normalize_quot_def Let_def mult.commute [of _ "unit_factor b"] dvd_div_mult2_eq mult_unit_dvd_iff')

definition normalized_fracts :: "('a :: {ring_gcd,idom_divide} × 'a) set" where
"normalized_fracts = {(a,b). coprime a b  unit_factor b = 1}"

lemma not_normalized_fracts_0_denom [simp]: "(a, 0)  normalized_fracts"
by (auto simp: normalized_fracts_def)

lemma unit_factor_snd_normalize_quot [simp]:

by (simp add: normalize_quot_def case_prod_unfold Let_def dvd_unit_factor_div
mult_unit_dvd_iff unit_factor_mult unit_factor_gcd)

lemma snd_normalize_quot_nonzero [simp]: "snd (normalize_quot x)  0"
using unit_factor_snd_normalize_quot[of x]
by (auto simp del: unit_factor_snd_normalize_quot)

lemma normalize_quot_aux:
fixes a b
assumes "b  0"
defines "d  gcd a b * unit_factor b"
shows   "a = fst (normalize_quot (a,b)) * d" "b = snd (normalize_quot (a,b)) * d"
"d dvd a" "d dvd b" "d  0"
proof -
from assms show "d dvd a" "d dvd b"
thus "a = fst (normalize_quot (a,b)) * d" "b = snd (normalize_quot (a,b)) * d" "d  0"
by (auto simp: normalize_quot_def Let_def d_def b  0)
qed

lemma normalize_quotE:
assumes "b  0"
obtains d where "a = fst (normalize_quot (a,b)) * d" "b = snd (normalize_quot (a,b)) * d"
"d dvd a" "d dvd b" "d  0"
using that[OF normalize_quot_aux[OF assms]] .

lemma normalize_quotE':
assumes "snd x  0"
obtains d where "fst x = fst (normalize_quot x) * d" "snd x = snd (normalize_quot x) * d"
"d dvd fst x" "d dvd snd x" "d  0"
proof -
from normalize_quotE[OF assms, of "fst x"] obtain d where
"fst x = fst (normalize_quot (fst x, snd x)) * d"
"snd x = snd (normalize_quot (fst x, snd x)) * d"
"d dvd fst x"
"d dvd snd x"
"d  0" .
then show ?thesis unfolding prod.collapse by (intro that[of d])
qed

lemma coprime_normalize_quot:
"coprime (fst (normalize_quot x)) (snd (normalize_quot x))"
by (simp add: normalize_quot_def case_prod_unfold div_mult_unit2)
(metis coprime_mult_self_right_iff div_gcd_coprime unit_div_mult_self unit_factor_is_unit)

lemma normalize_quot_in_normalized_fracts [simp]:
by (simp add: normalized_fracts_def coprime_normalize_quot case_prod_unfold)

lemma normalize_quot_eq_iff:
assumes "b  0" "d  0"
shows   "normalize_quot (a,b) = normalize_quot (c,d)  a * d = b * c"
proof -
define x y where "x = normalize_quot (a,b)" and "y = normalize_quot (c,d)"
from normalize_quotE[OF assms(1), of a] normalize_quotE[OF assms(2), of c]
obtain d1 d2
where "a = fst x * d1" "b = snd x * d1" "c = fst y * d2" "d = snd y * d2" "d1  0" "d2  0"
unfolding x_def y_def by metis
hence "a * d = b * c  fst x * snd y = snd x * fst y" by simp
also have "  fst x = fst y  snd x = snd y"
by (intro coprime_crossproduct') (simp_all add: x_def y_def coprime_normalize_quot)
also have "  x = y" using prod_eqI by blast
finally show "x = y  a * d = b * c" ..
qed

lemma normalize_quot_eq_iff':
assumes "snd x  0" "snd y  0"
shows
using assms by (cases x, cases y, hypsubst) (subst normalize_quot_eq_iff, simp_all)

lemma normalize_quot_id:
by (auto simp: normalized_fracts_def normalize_quot_def case_prod_unfold)

lemma normalize_quot_idem [simp]:
by (rule normalize_quot_id) simp_all

lemma fractrel_iff_normalize_quot_eq:

by (cases x, cases y) (auto simp: fractrel_def normalize_quot_eq_iff)

lemma fractrel_normalize_quot_left:
assumes "snd x  0"
shows   "fractrel (normalize_quot x) y  fractrel x y"
using assms by (subst (1 2) fractrel_iff_normalize_quot_eq) auto

lemma fractrel_normalize_quot_right:
assumes "snd x  0"
shows   "fractrel y (normalize_quot x)  fractrel y x"
using assms by (subst (1 2) fractrel_iff_normalize_quot_eq) auto

lift_definition quot_of_fract ::
"'a :: {ring_gcd,idom_divide,semiring_gcd_mult_normalize} fract  'a × 'a"
is normalize_quot
by (subst (asm) fractrel_iff_normalize_quot_eq) simp_all

lemma quot_to_fract_quot_of_fract [simp]:
unfolding quot_to_fract_def
proof transfer
fix x :: "'a × 'a" assume rel: "fractrel x x"
define x' where "x' = normalize_quot x"
obtain a b where [simp]: "x = (a, b)" by (cases x)
from rel have "b  0" by simp
from normalize_quotE[OF this, of a] obtain d
where
"a = fst (normalize_quot (a, b)) * d"
"b = snd (normalize_quot (a, b)) * d"
"d dvd a"
"d dvd b"
"d  0" .
hence "a = fst x' * d" "b = snd x' * d" "d  0" "snd x'  0" by (simp_all add: x'_def)
thus "fractrel (case x' of (a, b)  if b = 0 then (0, 1) else (a, b)) x"
qed

lemma quot_of_fract_quot_to_fract:
proof (cases "snd x = 0")
case True
thus ?thesis unfolding quot_to_fract_def
by transfer (simp add: case_prod_unfold normalize_quot_def)
next
case False
thus ?thesis unfolding quot_to_fract_def by transfer (simp add: case_prod_unfold)
qed

lemma quot_of_fract_quot_to_fract':

unfolding quot_to_fract_def by transfer (auto simp: normalize_quot_id)

lemma quot_of_fract_in_normalized_fracts [simp]:
by transfer simp

lemma normalize_quotI:
assumes "a * d = b * c" "b  0" "(c, d)  normalized_fracts"
shows   "normalize_quot (a, b) = (c, d)"
proof -
from assms have "normalize_quot (a, b) = normalize_quot (c, d)"
by (subst normalize_quot_eq_iff) auto
also have " = (c, d)" by (intro normalize_quot_id) fact
finally show ?thesis .
qed

lemma td_normalized_fract:

assumes "snd x  0" "snd y  0"
shows
proof -
from normalize_quotE'[OF assms(1)] obtain d
where d:
"fst x = fst (normalize_quot x) * d"
"snd x = snd (normalize_quot x) * d"
"d dvd fst x"
"d dvd snd x"
"d  0" .
from normalize_quotE'[OF assms(2)] obtain e
where e:
"fst y = fst (normalize_quot y) * e"
"snd y = snd (normalize_quot y) * e"
"e dvd fst y"
"e dvd snd y"
"e  0" .
show ?thesis by (simp_all add: d e algebra_simps)
qed

locale fract_as_normalized_quot
begin
setup_lifting td_normalized_fract
end

"quot_of_fract (x + y) =
(let (a,b) = quot_of_fract x; (c,d) = quot_of_fract y
in  normalize_quot (a * d + b * c, b * d))"

lemma quot_of_fract_uminus:
"quot_of_fract (-x) = (let (a,b) = quot_of_fract x in (-a, b))"
by transfer (auto simp: case_prod_unfold Let_def normalize_quot_def dvd_neg_div mult_unit_dvd_iff)

lemma quot_of_fract_diff:
"quot_of_fract (x - y) =
(let (a,b) = quot_of_fract x; (c,d) = quot_of_fract y
in  normalize_quot (a * d - b * c, b * d))" (is "_ = ?rhs")
proof -
have "x - y = x + -y" by simp
also have "quot_of_fract  = ?rhs"
by (simp only: quot_of_fract_add quot_of_fract_uminus Let_def case_prod_unfold) simp_all
finally show ?thesis .
qed

lemma normalize_quot_mult_coprime:
assumes "coprime a b" "coprime c d"
defines "e  fst (normalize_quot (a, d))" and "f  snd (normalize_quot (a, d))"
and  "g  fst (normalize_quot (c, b))" and "h  snd (normalize_quot (c, b))"
shows   "normalize_quot (a * c, b * d) = (e * g, f * h)"
proof (rule normalize_quotI)
from assms have "gcd a b = 1" "gcd c d = 1"
by simp_all
from assms have "b  0" "d  0" by auto
with assms have "normalize b = b" "normalize d = d"
by (auto intro: normalize_unit_factor_eqI)
from normalize_quotE [OF b  0, of c] obtain k
where
"c = fst (normalize_quot (c, b)) * k"
"b = snd (normalize_quot (c, b)) * k"
"k dvd c" "k dvd b" "k  0" .
note k = this [folded gcd a b   gcd c d   assms(3) assms(4)]
from normalize_quotE [OF d  0, of a] obtain l
where "a = fst (normalize_quot (a, d)) * l"
"d = snd (normalize_quot (a, d)) * l"
"l dvd a" "l dvd d" "l  0" .
note l = this [folded gcd a b   gcd c d   assms(3) assms(4)]
from k l show "a * c * (f * h) = b * d * (e * g)"
by (metis e_def f_def g_def h_def mult.commute mult.left_commute)
from assms have [simp]:
by simp_all
from assms have "coprime e f" "coprime g h" by (simp_all add: coprime_normalize_quot)
with k l assms(1,2) b  0 d  0
normalize b = b normalize d = d
show "(e * g, f * h)  normalized_fracts"
by (simp add: normalized_fracts_def unit_factor_mult e_def f_def g_def h_def
coprime_normalize_quot dvd_unit_factor_div unit_factor_gcd)
(metis coprime_mult_left_iff coprime_mult_right_iff)
qed (insert assms(3,4), auto)

lemma normalize_quot_mult:
assumes "snd x  0" "snd y  0"
shows
proof -
from normalize_quotE'[OF assms(1)] obtain d where d:
"fst x = fst (normalize_quot x) * d"
"snd x = snd (normalize_quot x) * d"
"d dvd fst x"
"d dvd snd x"
"d  0" .
from normalize_quotE'[OF assms(2)] obtain e where e:
"fst y = fst (normalize_quot y) * e"
"snd y = snd (normalize_quot y) * e"
"e dvd fst y"
"e dvd snd y"
"e  0" .
show ?thesis by (simp_all add: d e algebra_simps normalize_quot_eq_iff)
qed

lemma quot_of_fract_mult:
"quot_of_fract (x * y) =
(let (a,b) = quot_of_fract x; (c,d) = quot_of_fract y;
(e,f) = normalize_quot (a,d); (g,h) = normalize_quot (c,b)
in  (e*g, f*h))"
by transfer
(simp add: split_def Let_def coprime_normalize_quot normalize_quot_mult normalize_quot_mult_coprime)

lemma normalize_quot_0 [simp]:
"normalize_quot (0, x) = (0, 1)" "normalize_quot (x, 0) = (0, 1)"

lemma normalize_quot_eq_0_iff [simp]:
by (auto simp: normalize_quot_def case_prod_unfold Let_def div_mult_unit2 dvd_div_eq_0_iff)

lemma fst_quot_of_fract_0_imp: "fst (quot_of_fract x) = 0  snd (quot_of_fract x) = 1"
by transfer auto

lemma normalize_quot_swap:
assumes "a  0" "b  0"
defines "a'  fst (normalize_quot (a, b))" and "b'  snd (normalize_quot (a, b))"
shows   "normalize_quot (b, a) = (b' div unit_factor a', a' div unit_factor a')"
proof (rule normalize_quotI)
from normalize_quotE[OF assms(2), of a] obtain d where
"a = fst (normalize_quot (a, b)) * d"
"b = snd (normalize_quot (a, b)) * d"
"d dvd a" "d dvd b" "d  0" .
note d = this [folded assms(3,4)]
show "b * (a' div unit_factor a') = a * (b' div unit_factor a')"
using assms(1,2) d
by (simp add: div_unit_factor [symmetric] unit_div_mult_swap mult_ac del: div_unit_factor)
have "coprime a' b'" by (simp add: a'_def b'_def coprime_normalize_quot)
thus "(b' div unit_factor a', a' div unit_factor a')  normalized_fracts"
using assms(1,2) d
by (auto simp add: normalized_fracts_def ac_simps dvd_div_unit_iff elim: coprime_imp_coprime)
qed fact+

lemma quot_of_fract_inverse:
"quot_of_fract (inverse x) =
(let (a,b) = quot_of_fract x; d = unit_factor a
in  if d = 0 then (0, 1) else (b div d, a div d))"
proof (transfer, goal_cases)
case (1 x)
from normalize_quot_swap[of "fst x" "snd x"] show ?case
by (auto simp: Let_def case_prod_unfold)
qed

lemma normalize_quot_div_unit_left:
fixes x y u
assumes "is_unit u"
defines "x'  fst (normalize_quot (x, y))" and "y'  snd (normalize_quot (x, y))"
shows "normalize_quot (x div u, y) = (x' div u, y')"
proof (cases "y = 0")
case False
define v where "v = 1 div u"
with is_unit u have "is_unit v" and u: "a. a div u = a * v"
by simp_all
from is_unit v have "coprime v = top"
from normalize_quotE[OF False, of x] obtain d where
"x = fst (normalize_quot (x, y)) * d"
"y = snd (normalize_quot (x, y)) * d"
"d dvd x" "d dvd y" "d  0" .
note d = this[folded assms(2,3)]
from assms have "coprime x' y'" "unit_factor y' = 1"
with d coprime v = top have "normalize_quot (x * v, y) = (x' * v, y')"
by (auto simp: normalized_fracts_def intro: normalize_quotI)
then show ?thesis

lemma normalize_quot_div_unit_right:
fixes x y u
assumes "is_unit u"
defines "x'  fst (normalize_quot (x, y))" and "y'  snd (normalize_quot (x, y))"
shows "normalize_quot (x, y div u) = (x' * u, y')"
proof (cases "y = 0")
case False
from normalize_quotE[OF this, of x]
obtain d where d:
"x = fst (normalize_quot (x, y)) * d"
"y = snd (normalize_quot (x, y)) * d"
"d dvd x" "d dvd y" "d  0" .
note d = this[folded assms(2,3)]
from assms have "coprime x' y'" "unit_factor y' = 1" by (simp_all add: coprime_normalize_quot)
with d is_unit u show ?thesis
by (auto simp add: normalized_fracts_def is_unit_left_imp_coprime unit_div_eq_0_iff intro: normalize_quotI)

lemma normalize_quot_normalize_left:
fixes x y u
defines "x'  fst (normalize_quot (x, y))" and "y'  snd (normalize_quot (x, y))"
shows "normalize_quot (normalize x, y) = (x' div unit_factor x, y')"
using normalize_quot_div_unit_left[of "unit_factor x" x y]
by (cases "x = 0") (simp_all add: assms)

lemma normalize_quot_normalize_right:
fixes x y u
defines "x'  fst (normalize_quot (x, y))" and "y'  snd (normalize_quot (x, y))"
shows "normalize_quot (x, normalize y) = (x' * unit_factor y, y')"
using normalize_quot_div_unit_right[of "unit_factor y" x y]
by (cases "y = 0") (simp_all add: assms)

lemma quot_of_fract_0 [simp]: "quot_of_fract 0 = (0, 1)"
by transfer auto

lemma quot_of_fract_1 [simp]: "quot_of_fract 1 = (1, 1)"
by transfer (rule normalize_quotI, simp_all add: normalized_fracts_def)

lemma quot_of_fract_divide:
"quot_of_fract (x / y) = (if y = 0 then (0, 1) else
(let (a,b) = quot_of_fract x; (c,d) = quot_of_fract y;
(e,f) = normalize_quot (a,c); (g,h) = normalize_quot (d,b)
in  (e * g, f * h)))" (is "_ = ?rhs")
proof (cases "y = 0")
case False
hence A: "fst (quot_of_fract y)  0" by transfer auto
have "x / y = x * inverse y" by (simp add: divide_inverse)
also from False A have "quot_of_fract  = ?rhs"
by (simp only: quot_of_fract_mult quot_of_fract_inverse)
normalize_quot_div_unit_left normalize_quot_div_unit_right
normalize_quot_normalize_right normalize_quot_normalize_left)
finally show ?thesis .
qed simp_all

lemma snd_quot_of_fract_nonzero [simp]: "snd (quot_of_fract x)  0"
by transfer simp

lemma Fract_quot_of_fract [simp]: "Fract (fst (quot_of_fract x)) (snd (quot_of_fract x)) = x"
by transfer (simp del: fractrel_iff, subst fractrel_normalize_quot_left, simp)

lemma snd_quot_of_fract_Fract_whole:
assumes "y dvd x"
shows   "snd (quot_of_fract (Fract x y)) = 1"
using assms by transfer (auto simp: normalize_quot_def Let_def gcd_proj2_if_dvd)

lemma fst_quot_of_fract_eq_0_iff [simp]: "fst (quot_of_fract x) = 0  x = 0"
by transfer simp

lemma coprime_quot_of_fract:
"coprime (fst (quot_of_fract x)) (snd (quot_of_fract x))"